IMPLEMETATION OF EXPERIENTIAL LEARNING IN IMPROVING COLLAGE STUDENTS' CRITICAL THINKING SKILL: PENERAPAN EXPERIENTIAL LEARNING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA - Septiani, Mita; Mulyadi; Siregar, Eveline; Viona Septiavi Winarto Putri; Dikzi Adzkia Sutama Putri (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2025)
This study aims to describe the implementation of Experiential Learning in the course of using media and learning resources in improving students' critical thinking skills. In line with the objectives of the study, this study is included in descriptive research whose data is collected by conducting documentation studies, observations, interviews and distributing questionnaires. The study was conducted with respondents of two groups of Educational Technology (UNJ) undergraduate students in the fourth semester (4), academic year 2023/2024. This study produces procedures or guidelines for implementing EL in the course of using media and learning resources. Learning in the course of using media and learning resources that applies Experiential Learning takes place effectively through a continuous cycle of experience, reflection, conceptualization, and experimentation.